2019
DOI: 10.1002/er.4791
|View full text |Cite
|
Sign up to set email alerts
|

Application of a ground source heat pump system with PCM‐embedded radiant wall heating for buildings

Abstract: Summary This paper deals with the utilization of a renewable energy‐based integrated system with the latent heat storage option for building thermal management systems. Both energy and exergy‐based assessments of the current combined system are conducted. For this purpose, phase change material (PCM)‐embedded radiant wall heating system using solar heating and ground source heat pump (GSHP) is studied thermodynamically. Heat is essentially stored within the PCMs as used in the panels to increase the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Furthermore, the constant temperature of phase change improved the BHE extraction rate. Another work ( [31]) presented the exergy analysis of a hybrid GSHP system, coupled with solar panels, and indoor air conditioning was possible because of radiant panels with encapsulated PCM. The results showed that PCM was beneficial in term of first and second law efficiency; it increased with density and melting temperature.…”
mentioning
confidence: 99%
“…Furthermore, the constant temperature of phase change improved the BHE extraction rate. Another work ( [31]) presented the exergy analysis of a hybrid GSHP system, coupled with solar panels, and indoor air conditioning was possible because of radiant panels with encapsulated PCM. The results showed that PCM was beneficial in term of first and second law efficiency; it increased with density and melting temperature.…”
mentioning
confidence: 99%
“…The building thermal comfort can be improved by passive and active or sometimes hybrid solar designs . Moreover, outdoor temperature changes and daily solar energy can be retrieved using passive solar grids including thermal energy storage (TES) setups . In this regard, compared with sensible heat‐based systems, the popularity of latent heat‐based TES frameworks working by phase change materials (PCMs) is increased day by day because they allow higher heat storage per volume and also provide better management to the released heat …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Moreover, outdoor temperature changes and daily solar energy can be retrieved using passive solar grids including thermal energy storage (TES) setups. 4,5 In this regard, compared with sensible heat-based systems, the popularity of latent heat-based TES frameworks working by phase change materials (PCMs) is increased day by day because they allow higher heat storage per volume and also provide better management to the released heat. [6][7][8][9] Many solid-liquid PCMs (S-LPCMs) include organic and inorganic or their binary/ternary which have been used in various TES purposes such as thermal regulation of buildings, thermal management of foods, storing of waste heat, and cooling of electronic systems and photovoltaic panels.…”
Section: Introductionmentioning
confidence: 99%
“…3 Thermal energy storage (TES) method using with phase change materials (PCMs) has been growing interest due to decreasing heating, ventilation, and air conditioning times while it saves energy and reduces fossil fuel consumption and as well as pollutant emissions. [13][14][15] PCMs are capable materials for absorbing and releasing large amounts of thermal energy in latent heat form via phase-changing process. PCMs offer improving the energy efficiency in building and reducing the fossil sourcedenergy consumption.…”
Section: Introductionmentioning
confidence: 99%